ANALISIS FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Y Yanti (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2017)
This research was conducted to analyze the factors that influence dividend payout ratio. The reason researchers choose a manufacturing company as an object of research because the manufacturing company is a company that has a continuous production activities, so to maintain the continuity of the company requires a large fund. This study took a sample manufacturing companies listed on the Indonesia Stock Exchange 2010-2013 period. Methods of data analysis using multiple regression to include classical assumptions consisting of normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. The results showed that only ROA and Leverage variables that have an influence on Dividend Payout Ratio. The implications of these results contributing to managers may be to consider using an analysis of Return on Assets and Leverage that reflect the value of the firm's debt. to predict the behavior of corporate dividend policies. So to invest in capital market activities, the stock market value can be predicted by using these factors